2017
DOI: 10.1038/srep44646
|View full text |Cite
|
Sign up to set email alerts
|

To Find a Better Dosimetric Parameter in the Predicting of Radiation-Induced Lung Toxicity Individually: Ventilation, Perfusion or CT based

Abstract: This study aimed to find a better dosimetric parameter in predicting of radiation-induced lung toxicity (RILT) in patients with non-small cell lung cancer (NSCLC) individually: ventilation(V), perfusion (Q) or computerized tomography (CT) based. V/Q single-photon emission computerized tomography (SPECT) was performed within 1 week prior to radiotherapy (RT). All V/Q imaging data was integrated into RT planning system, generating functional parameters based on V/Q SPECT. Fifty-seven NSCLC patients were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…Similar results were obtained in another study (92). Recent studies have shown that SPECT/CT-based ventilation and perfusion functional LDVP are used to predict RILI, indicating that if the patient has central-type NSCLC or chronic obstructive pulmonary disease, ventilation-based (V-fV 20 , V-f-MLD) is better than perfusion-based (Q-fV 20 , Q-f-MLD) to predict RILI (93).…”
Section: Predicting Radiation Pneumonitissupporting
confidence: 81%
“…Similar results were obtained in another study (92). Recent studies have shown that SPECT/CT-based ventilation and perfusion functional LDVP are used to predict RILI, indicating that if the patient has central-type NSCLC or chronic obstructive pulmonary disease, ventilation-based (V-fV 20 , V-f-MLD) is better than perfusion-based (Q-fV 20 , Q-f-MLD) to predict RILI (93).…”
Section: Predicting Radiation Pneumonitissupporting
confidence: 81%